'Death and axes': unexpected Ca²⁺ entry phenologs predict new anti-schistosomal agents. - John D Chan; Prince N Agbedanu; Mostafa Zamanian; Sarah M Gruba; Christy L Haynes; Timothy A Day; Jonathan S Marchant (PLoS Pathogens)
Schistosomiasis is a parasitic flatworm disease that infects 200 million people worldwide. The drug praziquantel (PZQ) is the mainstay therapy but the target of this drug remains ambiguous. While PZQ paralyses and kills parasitic schistosomes, in free-living planarians PZQ caused an unusual axis duplication during regeneration to yield two-headed animals. Here, we show that PZQ activation of a neuronal Ca²⁺ channel modulates opposing dopaminergic and serotonergic pathways to regulate 'head' structure formation. Surprisingly, compounds with efficacy for either bioaminergic network in planarians also displayed antischistosomal activity, and reciprocally, agents first identified as antischistocidal compounds caused bipolar regeneration in the planarian bioassay. These divergent outcomes (death versus axis duplication) result from the same Ca²⁺ entry mechanism, and comprise unexpected Ca²⁺ phenologs with meaningful predictive value. Surprisingly, basic research into axis patterning mechanisms provides an unexpected route for discovering novel antischistosomal agents.